Comparison of systemic and local methotrexate treatments in cesarean scar pregnancies: time to change conventional treatment and follow-up protocols. (November 2016) - Uludag, Semih Z.; Kutuk, Mehmet S.; Ak, Mehmet; Ozgun, Mahmut T.; Dolanbay, Mehmet; Aygen, Ercan M.; Sahin, Yılmaz
Abstract: Objective: The aim of this study was to compare the use of systemic and local methotrexate in the treatment of cesarean scar pregnancy. Study design: In this retrospective cohort study, we collected the data of 44 patients with cesarean scar pregnancy. The patients were grouped according to treatment modality: Group 1, local methotrexate injection (n = 17) and Group 2, systemic methotrexate (n = 27). The groups were compared with respect to side effects, recovery time, reproductive outcome, and treatment cost. Results: The mean gestational age at diagnosis (6.4 ± 0.93 vs. 5.4 ± 0.80 weeks, p = 0.001), pretreatment serum β-human chorionic gonadotrophin level [27, 970 (11, 010–39, 421) vs. 7606 (4725–16, 996) mIU/mL, p = 0.001], and lesion size (2.74 ± 1.36 and 1.28 ± 0.55 cm, p = 0.001) were higher in Group 1. All patients were cured by primary therapy without additional surgery. The mean times for β-human chorionic gonadotrophin normalization, the uterine-mass disappearance, were significantly shorter in Group 1 than in Group 2 (6.17 ± 1.55 vs. 8.11 ± 2.0 weeks, p = 0.001 and 10.47 ± 4.14 vs. 13.40 ± 4.44 weeks, p = 0.002, respectively). The cost of treatment was similar between groups (281.133 ± 112.123 vs. 551.134 ± 131.792 , p = 0.76). The total pregnancy rates were not different between groups (5/16, 31.4% vs. 6/11, 54.6%, p = 0.301). One recurrent cesarean scar pregnancy occurred after systemic methotrexate. Oral ulcers, the most common side effect, were seen in seven patients in Group 2. Conclusion: Even though treatment success and reproductive outcomes are similar, local methotrexate is superior to systemic methotrexate with regard to recovery time, side effects, and treatment costs, even in patients with unfavorable pretreatment prognostic predictors.